UPAYA DINAS PERPUSTAKAAN DALAM MENINGKATKAN MUTU PELAYANAN (studi Dinas Perpustakaan dan Kearsipan Kabupaten Jember) - Edhi Siswanto; Ika Herawati (Universitas Muhammadiyah Jember, 2018)
ABSTRACT This study aims to find out the efforts of Library Office in improving the quality of service (study of the Library and Archives Office of Jember Regency). This type of research uses qualitative research with a descriptive approach. Data sources are obtained from primary and secondary data. Collecting data through observation, interviews and documentation. The analysis uses data analysis of interactive models which include, Data Collection, Data Reduction, Data Presentation and Conclusing Drawing / Verification. The results showed that there were several efforts of the Library Service in improving the quality of service which could be measured using management theory with 4 factors namely Planning, Organizing, Actuating, Controlling but these efforts had not been maximized due to constraints on the quality of human resources is minimalKeywords: Effort, Library, Reading Interest, Service Quality